(3QSGdI GdQO HPcQ GdeYGOs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd dChdjGA Ojfg GdadL hGdZdH hLYd OGFQg GdShA Ydi ef fcU Ydi YbHjg hGfbdH hChLH GddYf s
(3BNQgG (B:s
(3heeG ChQOJg ai gPg GdQSGdI ebGdhf aPQge jNVhf hjdYHhf MJi jdGbhG jhege GdPi cGfhG Hg jhgOhf hGdMeO ddg GdHGQ ehdi GdYGdejf HhSGWI hdjg GdbGFe dfLGI GdehMOjf hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B69s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds